Hot electron-driven SERS enhancement of non-SERS-active creatinine using Ag-decorated ZnO nanorods - N.A. Abdullah; M.Z.A. Razak; T.H.T. Aziz; A.R.M. Zain; M.S.M. Jamil; M.M. Salleh (Results in Chemistry)
The development of highly sensitive and selective Surface-Enhanced Raman Spectroscopy (SERS) substrates is crucial for biomedical applications. This study presents an advanced SERS substrate by integrating silver nanoparticles (AgNPs) with ZnO nanorods (NRs), leveraging hot electron dynamics to enhance the SERS signal for non-SERS-active creatinine detection. AgNPs were deposited onto ZnO NRs using silver nitrate (AgNO₃) concentrations ranging from 0.01 M to 0.16 M, resulting in distinct nanoparticle distributions optimized for hot electron generation. The structural and optical properties of the substrates were systematically analyzed using FESEM, EDX mapping, and UV–Vis spectroscopy. The AgZnO nanorods synthesized with 0.13 M AgNO₃ demonstrated the most favorable AgNPs distribution, achieving a high-density configuration that significantly enhanced the Raman signal, yielding an enhancement factor (EF) of 5.07 × 103 for 1.0 × 10−2 M non-SERS-active creatinine molecules, representing a 56.90 % improvement in sensitivity. This enhancement is attributed to the synergistic effect of localized surface plasmon resonance (LSPR) and efficient hot electron transfer, facilitated by the optimized AgNPs distribution. Moreover, the substrate showed strong reproducibility (RSD < 30 %), short-term stability over five days, and uniform SERS activity across the surface. These findings establish a direct correlation between AgNPs arrangement and hot electron-driven SERS enhancement, highlighting the potential of AgZnO nanorods as a highly effective SERS substrate for biomedical applications.